Analisis Peran Manajemen SDM dalam Menjaga Kepatuhan Hukum di Era E-Commerce - Alfayda Khaerani; Nurul Ridati; Ridwan Ridwan; Muhamad Muslim; Abdul Wahid Alfarizi (Pusat Riset dan Inovasi Nasional, 2026)
The establishment of a corporate legal framework is essential in providing legal protection for companies, employees, clients, and other stakeholders involved in business activities. In the digital era, rapid business development, particularly in the E-Commerce sector, has created new challenges related to legal compliance. The increasing use of digital platforms has exposed companies to various legal risks, including online fraud, data breaches, privacy violations, and non-compliance with applicable regulations. Therefore, organizations must implement effective strategies to ensure compliance with legal and regulatory requirements. This study aims to analyze the role of Human Resource (HR) Management in maintaining legal compliance within the E-Commerce environment. The research employs a normative juridical approach with descriptive analysis based on a comprehensive literature review of relevant laws, regulations, and academic sources. The findings reveal that HR Management plays a strategic role in promoting legal compliance through employee training programs, the development and implementation of internal policies, monitoring employee conduct, and supervising company operations. HR also contributes to fostering a culture of compliance and ethical behavior within the organization. Effective HR management can minimize the risk of legal violations, enhance consumer trust, strengthen corporate reputation, and support long-term business sustainability in the increasingly competitive digital marketplace.